A FUZZY-BASED DECISION MAKING APPROACH FOR PRODUCT CONCEPT SELECTION - Ade Febransyah; J. Bely Utarja (Institute of Research and Community Outreach - Petra Christian University, 2004)
Selecting the best product concept is one of critical tasks in product development process. Making decisions at this stage becomes very difficult due to imprecise and uncertain product requirements. This paper presents the framework of product concept selection that integrates the fuzzy set theory and the analytic hierarchy process (AHP). In the proposed approach, the fuzzy membership function is employed in performing